2014
DOI: 10.1007/s11605-014-2525-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Complication Following Gastrectomy for Gastric Cancer: Retrospective Analysis of Prospectively Collected Data Based on the Clavien–Dindo System

Abstract: Age and the extent of gastrectomy were revealed as the prognostic factors for overall complications and the complications of grade IIIa or over according to the Clavien-Dindo classification following gastrectomy for gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
79
4
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(103 citation statements)
references
References 31 publications
14
79
4
6
Order By: Relevance
“…Previous studies reported that age was a significant predictive factor for postoperative morbidity after gastric cancer surgery [8,9]. In our study, consistent with these studies, the overall morbidity rate was higher in the elderly group (26.3 vs. 16.1%, p < 0.001), while there were no significant differences in operative factors such as the type of gastrectomy, extent of lymph node dissection, or combined resection of the spleen and/or pancreas.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies reported that age was a significant predictive factor for postoperative morbidity after gastric cancer surgery [8,9]. In our study, consistent with these studies, the overall morbidity rate was higher in the elderly group (26.3 vs. 16.1%, p < 0.001), while there were no significant differences in operative factors such as the type of gastrectomy, extent of lymph node dissection, or combined resection of the spleen and/or pancreas.…”
Section: Discussionsupporting
confidence: 91%
“…In our records they are represented by only 4 patients (5.4%). However, similar results were reported by other studies in larger series [2].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, age is not a significant risk factor for complications, conversely other studies [2] [14] consider it a risk factor and the authors discourage this kind of surgery in older people.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…It plays a key role in maintaining colloid osmotic pressure, as well as acting as a transport vehicle for intrinsic metabolites, drugs, and anti-oxidative agents [11]. Low serum albumin reflects inflammatory activity and has been reported as a risk factor of post-operative complications and survival in various cancer types [9,[12][13][14][15]]. …”
Section: Introductionmentioning
confidence: 99%